Comparative Analysis of Variables Causing Delays in the Construction of the Wiego Warehouse Building, Jalan Letda Sujono, Medan - Siregar, Muhammad Risky Qamad; Sarifah, Jupriah; Simbolon, Ronal H T (CV. Rayyan Dwi Bharata, 2024)
Construction projects are of course carried out in accordance with the implementation plan which is prepared based on the letter of agreement, general contract conditions, special contract conditions and technical specifications. In this plan, it is determined when the project must start and when the project must be finished. In every construction project, of course all parties involved want the project to be completed on time as previously determined. However, in reality, projects have their own problems and obstacles. One of the problems that really affects project performance in terms of time, quality and cost is the problem of project delays. In this study, a case study was carried out regarding the identification and analysis of factors causing delays in work on the Wiego Warehouse Building Construction project so that from the results of the analysis of factors causing delays, dominant factors and responses to handling them can be obtained. The Wiego Warehouse building is located on Jalan Letda Sujono, Medan and was built by contractor PT. Mitra Mandiri Asset Indo. This became the basis for conducting this research. The aim of this research is to determine the causes/risk factors that have a high level (dominant) and risk management responses that have a high level, in order to improve contractor performance. The research used is descriptive, using a questionnaire as a research instrument. Study of factors causing delays using the risk frequency scale, risk impact scale, and risk analysis matrix. The research results show that risk events are included in the classification of causal factors/high risk (high risk), which are significant for the problem of delays in building project implementation and the handling response to risk events that have a high ratio level. The dominant factor factor causing delays has a Severity index value of 61% - 80% and a risk level value of 16 (sixteen). For handling, there are several handling actions for dominant risks. Handling is carried out to minimize factors that cause delays and avoid sanctions or fines.